Sekam Padi Untuk Proses Pack Karburising Baja Karbon Rendah - Arianto Leman Soemowidagdo (Semesta Teknika, 2009)
The effectiveness of rice husk on pack carburizing process of low-carbon steel was investigated. The process was carried out at 850°C for 2, 4 and 6 hours. Carbon content of the specimen materials is 0.082%. Rice husk charcoal and rice husk powder was then compared to graphite powder. All of the media were sifted on 50 mesh sieve. After the process, all specimens were reheated up to 850°C, and then, hold it for 5 minutes. Subsequently, they were quenched into water at 28°C. The result shows that the effectiveness of rice husk charcoal is better than those of other media being used in the investigation. Six hours pack carburizing utilized, rice husk charcoal resulted in the enhancement of steel surface hardness from 122 VHN to 465 VHN and increase of the proportion of martensite structure.